DIMENSI KECERDASAN MAJEMUK DALAM KURIKULUM 2013 - Imam Machali (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
This paper aims to reveal the relevance of changing and developing of 2013 curriculum with nine intelligences theory (multiple intelligences) developed by Howard Gardner. The results show that 2013 curriculum contains the development dimension of multiple intelligences that can be seen in three areas, the first is the development of competencies which consists of four competency cores; those are spiritual attitude, social attitudes, knowledge and skills. In agrove of multiple intelligences, they belong to several kinds of intelligences such as the dimensions of existential, interpersonal, intrapersonal, linguistic, logical-mathematical, musical, visual/spatial, bodily-kinesthetic, and naturalist/environment intelligence. The second is in the approach used in the form of a scientific approach, including; observing, asking, trying, reasoning, and communicating. The third is the scoring system done by authentic assessment.